ANALYSIS OF THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY (CSR), COMPANY SIZE AND LEVERAGE ON FIRM VALUE WITH PROFITABILITY MEDIATION VARIABLES ON MINING COMPANY LISTED ON THE IDX (BEFORE COVID-19 2016-2019 AND DURING COVID-19 2020) - Nenshiria Septyaning Wibowo; Wita Ramadhanti; Triani Arofah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
The purpose of this study was to analyze the effect of Corporate Social Responsibility (CSR), company size, and leverage on firm value by using the moderating variable of profitability in mining companies listed on the IDX (2016-2020). The number of samples in the companies studied was 27 companies. The research used a purposive sampling method to determine the selection. Data analysis using multiple regression analysis and also an endurance test The results of this study are Corporate Social Responsibility (CSR) has no effect on firm value. Company size has no effect on firm value. Leverage has no significant effect on firm value. All moderating relation also variable cannot be proven. Hence this research then made supplementary test by divided the timeline after and during covid. The results shows that the insignificant of data due to different situation before covid and during covid. Before covid period (2016-2019) the results consistent with main hypothesis testing. Thus, during Covid-19 profitability moderate the relations between company size and firm value during 2020. The implication of this research is to help investors make investment decisions and help companies optimize the company.